2014
DOI: 10.1186/1472-6882-14-508
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity effect of degraded and undegraded kappa and iota carrageenan in human intestine and liver cell lines

Abstract: BackgroundCarrageenan is a linear sulphated polysaccharide extracted from red seaweed of the Rhodophyceae family. It has broad spectrum of applications in biomedical and biopharmaceutical field. In this study, we determined the cytotoxicity of degraded and undegraded carrageenan in human intestine (Caco-2; cancer and FHs 74 Int; normal) and liver (HepG2; cancer and Fa2N-4; normal) cell lines.MethodsFood grade k-carrageenan (FGKC), dried sheet k-carrageenan (DKC), commercial grade k-carrageenan (CGKC), food gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 70 publications
2
40
0
1
Order By: Relevance
“…For example, a 10 kDa carrageenan fraction obtained from native ι-carrageenan from Euchema spinosum by acid hydrolysis at high temperature did not induce colitis in rats while a 50 kDa fraction was colitogenic [ 84 ]. Inhibition of cell proliferation and induction of apoptosis was shown by a hydrocholic acid degraded κ-carrageenan in intestinal epithelial (Caco-2 and FHs 74 Int) and liver (HepG2 and Fa2N-4) cell lines [ 88 ].…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a 10 kDa carrageenan fraction obtained from native ι-carrageenan from Euchema spinosum by acid hydrolysis at high temperature did not induce colitis in rats while a 50 kDa fraction was colitogenic [ 84 ]. Inhibition of cell proliferation and induction of apoptosis was shown by a hydrocholic acid degraded κ-carrageenan in intestinal epithelial (Caco-2 and FHs 74 Int) and liver (HepG2 and Fa2N-4) cell lines [ 88 ].…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
“…The latter is characterized by having a greatly reduced molecular mass. While both types inhibit the expression of nitric oxide synthase, only dc-porphyran inhibits the consequent production of nitric oxide in LPS-stimulated RAW264.7 cells [ 88 ]. Likewise, dc-porphyran showed a slightly higher antioxidant activity.…”
Section: Red Seaweeds and Intestinal Mucosal Barrier Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have suggested carrageenans to have antitumoral activities. Another study reported apoptosis induction in human intestine (Caco-2) and hepatic (HepG2) cell lines, while no toxicity was observed on corresponding normal cell (Ariffin et al, 2014). Another study reported apoptosis induction in human intestine (Caco-2) and hepatic (HepG2) cell lines, while no toxicity was observed on corresponding normal cell (Ariffin et al, 2014).…”
Section: Carrageenansmentioning
confidence: 99%
“…The carrageenans suppressed the growth of breast, colon, liver, and osteosarcoma cell lines (30). In addition, carrageenan extracted from red seaweed of the Rhodophyceae family and L. papillosa showed cytotoxicity via inhibition of cell proliferation and induction of apoptosis in human intestinal cancer, breast cancer, and liver cancer cells (31,32). Consistent with the anticancer activity, the administration of λ-carrageenan stimulated the immune system via up-regulation of proinflammatory IL17A and TNF-α, thereby stimulating the activities of tumor infiltrating M1 macrophages, dendritic cells, and T lymphocytes (33).…”
Section: Inhibition Of Cancer Cell Proliferation and Survival Bymentioning
confidence: 98%